#TITLE_ALTERNATIVE# - NURWULAN (NIM 10105009), INDAH
Wavelet or small wave is a family from basis function that used to approximate some function. The basic idea is to analyze with skala via representation some basis. The wavelet Haar basis is the simplest basis of Wavelet. Wavelet Haar can be used to solve the problem of calculus variation that find the trajectory or graphics of function wich have some constraints. The problem of calculus variation that have discussed in this final assignment is some function that have initial value but don't have end value and some function that have the both of initial value and end value. Wirtingers inequality is an inequality that we can validate as calculus variation wich have initial value and end value.